Increased brood size leads to persistent eroded telomeres - Reichert, Sophie; Stier, Antoine; Zahn, Sandrine; Arrivé, Mathilde; Bize, Pierre; Massemin, Sylvie; Criscuolo, François (Frontiers in Ecology and Evolution, 2014)
Costs of reproduction can be divided in mandatory costs coming from physiological, metabolic and anatomical changes required to sustain reproduction itself, and in investment-dependent costs that are likely to become apparent when reproductive efforts are exceeding what organisms were prepared to sustain. Interestingly, recent data showed that entering reproduction enhanced breeders’ telomere loss, but no data explored so far the impact of reproductive investment. Telomeres protect the ends of eukaryote chromosomes. Shortened telomeres were associated with shorter lifespan, telomere erosion being then proposed to powerfully quantify life’s insults. Here, we experimentally manipulated brood size in order to modify reproductive investment of adult zebra finches (Taeniopygia guttata) below or beyond their (optimal) starting investment and tested the consequences of our treatment on parents’ telomere dynamics. We show that an increased brood size led to a reduction in telomere lengths in both parents compared to control and to parents raising a reduced brood. This greater telomere erosion was detected in parents immediately after the reproductive event and the telomere length difference persisted up to one year later. However, we did not detect any effects of brood size manipulation on annual survival of parents kept under laboratory conditions. In addition, telomere lengths at the end of reproduction were not associated with annual survival. Altogether, although our findings highlight that fast telomere erosion can come as a cost of brood size manipulation, they provide mixed correlative support to the emerging hypothesis that telomere erosion could account for the links between high reproductive investment and longevity.